Combination of erlotinib and a PARP inhibitor inhibits growth of A2780 tumor xenografts due to increased autophagy - Sui H; Shi C; Yan Z; Li H (Dove Medical Press, 2015)
Hongying Sui, Caixia Shi, Zhipeng Yan, Hucheng LiDepartment of Gynecological Oncology, Hunan Cancer Hospital, The Affiliated Cancer Hospital of Xiangya School of Medicine, Central South University, Changsha City, People’s Republic of ChinaBackground: Ovarian cancer is the leading cause of death in women with gynecological malignancy worldwide. Despite multiple new approaches to treatment, relapse remains almost inevitable in patients with advanced disease. The poor outcome of advanced ovarian cancer treated with conventional therapy stimulated the search for new strategies to improve therapeutic efficacy. Although epidermal growth factor receptor (EGFR) and poly(ADP-ribose) polymerase (PARP) inhibitors have known activity in advanced ovarian cancer, the effect of combined therapy against EGFR and PARP in this population has not been reported. In the current study, we investigated the mechanisms of erlotinib used alone or in combination with olaparib (AZD2281), a potent inhibitor of PARP, in an EGFR-overexpressing ovarian tumor xenograft model.Methods: A2780 (EGFR-overexpressing, BRCA1/2 wild-type) cells were subcutaneously injected into nude mice, which were then randomly assigned to treatment with vehicle, erlotinib, AZD2281, or erlotinib + AZD2281, for up to 3 weeks. All mice were then sacrificed and tumor tissues were subjected to Western blot analysis and monodansylcadervarine staining (for analysis of autophagy).Results: Erlotinib could slightly inhibit growth of A2780 tumor xenografts, and AZD2281 alone had similar effects on tumor growth. However, the combination treatment had a markedly enhanced antitumor effect. Western blot analysis revealed that treatment with erlotinib could significantly reduce the phosphorylation level of ERK1/2 and AKT in A2780 tumor tissue. Of interest, monodansylcadervarine staining showed that the autophagic effects were substantially enhanced when the agents were combined, which may be due to downregulation of apoptosis.Conclusion: These results suggest that combination of a selective EGFR inhibitor and a PARP inhibitor is effective in ovarian cancer A2780 xenografts, and depends on enhanced autophagy.Keywords: erlotinib, poly(ADP-ribose) polymerase, PARP, olaparib, tyrosine kinase inhibitor, ovarian cancer, autophagy, apoptosis